Detektion antigen virus den on monocyts by streptavidin biotin test as early diagnostic for dengue fever haemorhagic - Y NINING SRI WURYANINGSIH (Biodiversitas Journal of Biological Diversity, 2007)
Dengue virus infection is the main cause of morbidity and mortality in the tropical and sub-tropical countries of the world. Clinically it may manifest as asymtomastic, undifferentiated fever,dengue fever,dengue haemorrhagic fever and dengue shock syndrome cases.. The mechanism underlying the disease with severe complication is not clear yet,however it has been previosus reported that primary andsecondary infections of dengue virus play an important role in the patogenesis of this diseases. Early diagnosis of dengue virus infection has a great contribution for appropriate management of the disease, especialy for the prognosis of the patient. Laboratory investigations for such cases will be methods on serological investigation as well as virus isolation and identification.of dengue virus infection could be madeby detection of specific virus ,viral antigen,genomic sequence and or detection of antibodies. These methods are sensitive and precise for detecting dengue virus infection,but there need special equipment,costly and detection of IgM and IgG often positive or negative false the dengue virus in the blood stream There for, this study was performed in order to develop a method to detect dengue virus antigen on the monocytes using Streptavidin biotin technique. The result of Streptavidin biotin study demonstrated that 32 sera from patient suspectedwith DHF 78,1% were positive DHF,and 21,9% were negative DHF. These results are consistent with the result from WHO criteria as standard .The Chi Square analysis showed that the presentage of sensitivity and specificity of Streptavidin biotin methode were 88% and 87,7% respectively. In conclusions ,immunocytochemistry method using streptavidin biotin technique could be used as a method to detect antigen dengue virus on monocytes in the serum patient suspected with DHF. This technique has high sensitivity and specivicity andconsistent with the clinical WHO criteria for DHF,Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Dengue Haemorrhagic ,Monocyte , Steptavidin biotin